Case study for the development and implementation of an environmental management system (GEON Journal (Management, Organizations and Business), 2019)
Environmental management has gained greater importance in the business environment in the last two decades. This is a result of the rise of new trade schemes arising from the growing globalization social, cultural and economic that has occurred through the markets opening prompted by many free trade agreements. The competitive environment has evolved into a much more difficult scenario. Is in this scenario, which the companies are increasingly aware of their social role and the contributions they should make with a view to achieving higher levels of economic integration, development, and growth. In this particular field has been studied the case of supermarket El Nazareno, located in Las Matas de Farfán, in the south of the Dominican Republic, whose environmental management has been the object of observation and produced results of great value and common interest. The goal of this study was to determine necessary adjustments to develop and implement an indicators based system to measure environmental management.
Keywords: Development; Enviroment; Growth; Indicators; Management; smes; Sustainability